Extraction and characterization of proteins from skim rubber - Nanticha Kalapat (2018)
To optimize the extraction of proteins from skim natural rubber (NR), solution type, number of extractions and sample size were examined. Two solutions, phosphate buffered saline (PBS) and sodium dodecyl sulfate (SDS), were used for protein extraction. The protein content was determined by Bradford assay. SDS-polyacrylamide gel electrophoresis (SDS-PAGE) was employed to check the molecular weight of the extract. Analysis of protein purity by Fourier Transform Infrared (FTIR), spectrometer UV-Vis spectrometer and Carbon-Hydroger-Nitrogen (CHN) analyzer was also carried out on the extract from skim NR and compared with bovine serum albumin (BSA), a model protein. The results revealed that all factors had significant effects on the levels of protein extracted. A high extractable protein (EP) content was obtained from the skim NR using a small amount of specimen in fresh SDS solution and repeating the extraction step three times (12 h/time). SDS-PAGE demonstrated that the EP had three subunit molecular weights of 66, 78 and 116 kDa. Protein impurities could be detected by the CHN method, infrared technique and UV absorbance analysis.